2017
DOI: 10.1038/s41598-017-06558-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the spatial patterns of water storage variation over China in recent 70 years

Abstract: Terrestrial water storage (TWS) variation is crucial for global hydrological cycles and water resources management under climatic changes. In the previous studies, changes in water storage of some part of China have been studied with GRACE data in recent ten years. However, the spatial pattern of changes in water storage over China may be different in a long period. Here, we aimed to present long-term spatial patterns of TWS over China between 1948 to 2015 by unique Global Land Data Assimilation System Version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…The TWSA time series derived from the GLDAS models have good correlations with those of GRACE observations in the Pearl River basin. Such good correlations have been reported in previous studies in the same basin (Chen et al, ; Luo et al, ). This is because human activities have lower influence to water storage changes and precipitation is the major recharge source of water storage in the Pearl River basin (Chen et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The TWSA time series derived from the GLDAS models have good correlations with those of GRACE observations in the Pearl River basin. Such good correlations have been reported in previous studies in the same basin (Chen et al, ; Luo et al, ). This is because human activities have lower influence to water storage changes and precipitation is the major recharge source of water storage in the Pearl River basin (Chen et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Such good correlations have been reported in previous studies in the same basin (Chen et al, ; Luo et al, ). This is because human activities have lower influence to water storage changes and precipitation is the major recharge source of water storage in the Pearl River basin (Chen et al, ). Thus, the conclusion should be drawn that the machine learning models can obtain comparable results with the GLDAS models in the Pearl River basin.…”
Section: Discussionmentioning
confidence: 99%
“…Between 1979 and the 2010s, water storage decreased significantly [36], and GWS decreased more significantly than TWS. As shown in Figure 3a, the number of TWSAs is less than 0 in most years.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous studies have reported the contribution and restriction of P to TWS. For instance, Chen et al (2017) revealed the liability of P to TWS (r=0.78) in the PRB. Mo et al (2016) found TWS more strongly explained (60%) by annual P in river basins in south China than in north China.…”
Section: Causal Roles Of Water and Dryness In Vegetation Changesmentioning
confidence: 99%